Hodgkin lymphoma as a rare cause of complete atrioventricular block: a case report - Ekaterina A. Pravkina; Dmitry S. Sinitsyn; Polina S. Vikulova; Ilya B. Glukhovets; Sergei V. Subbotin (КардиоСоматика)
INTRODUCTION: Complete atrioventricular block is a life-threatening condition that requires urgent intervention and pacemaker implantation. Determining the underlying cause of the block is essential for effective management. This article describes a rare clinical case of third-degree atrioventricular block caused by Hodgkin lymphoma.